2014
DOI: 10.2147/cmar.s52217
|View full text |Cite
|
Sign up to set email alerts
|

Proactive strategies for regorafenib in metastatic colorectal cancer: implications for optimal patient management

Abstract: Regorafenib is a broad-spectrum oral multikinase inhibitor that targets several angiogenic, oncogenic, and stromal receptor tyrosine kinases that support the tumor microenvironment. Results from the pivotal Phase III Patients with Metastatic Colorectal Cancer Treated with Regorafenib or Placebo After Failure of Standard Therapy (CORRECT) trial showed that the addition of regorafenib to best supportive care resulted in a significant improvement in median overall survival and progression-free survival compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Different FGFR specific inhibitors are currently under development [ 40 ], and further evaluation of their activity in the subset of colorectal cancer with FGFR/FGFRL1 alterations should be pursued. Moreover, Regorafenib, a multi-kinase inhibitor that targets FGFR1 among other RTKs, was recently approved by the FDA for the treatment of advanced colorectal cancer [ 41 ], but predictive biomarkers for this indication are not yet currently available.…”
Section: Resultsmentioning
confidence: 99%
“…Different FGFR specific inhibitors are currently under development [ 40 ], and further evaluation of their activity in the subset of colorectal cancer with FGFR/FGFRL1 alterations should be pursued. Moreover, Regorafenib, a multi-kinase inhibitor that targets FGFR1 among other RTKs, was recently approved by the FDA for the treatment of advanced colorectal cancer [ 41 ], but predictive biomarkers for this indication are not yet currently available.…”
Section: Resultsmentioning
confidence: 99%
“…These expert opinions are based on the prescribing information, clinical study data, and clinical practice guidelines, which state that regorafenib monitoring should be carried out weekly during the first 2 cycles of treatment and monthly thereafter, 75 with special attention to toxicities detected during prior cycles to prevent their worsening. 63,75,76 Similarly, trifluridine/tipiracil monitoring should be weekly or biweekly following treatment initiation. 8,27 Expert opinions from Korea and France describe a slightly different approach to patient monitoring in their clinics, with weekly followup only during the first cycle of treatment.…”
Section: Patient Monitoringmentioning
confidence: 99%
“…A recently published safety analysis from the CORRECT study found that the occurrence of these commonly encountered toxicities tend to peak in terms of severity during the earlier treatment cycles, and then became stable in later cycles [27]. Therefore, these common toxicities do not appear to be cumulative and should be manageable with the increasing availability of consensus guidelines on supportive treatment and prevention [28,29]. For instance, in the CORRECT study, 32% of regorafenib-treated patients experienced HFSR during cycle 1, but the incidence dropped to only 5% in cycle 8, suggesting that discontinuation due to this toxicity can be avoided with preemptive dermatological treatment and dose modifications [29].…”
Section: Toxicity Of Regorafenib In Clinical Trial and Community Settingmentioning
confidence: 99%
“…Therefore, these common toxicities do not appear to be cumulative and should be manageable with the increasing availability of consensus guidelines on supportive treatment and prevention [28,29]. For instance, in the CORRECT study, 32% of regorafenib-treated patients experienced HFSR during cycle 1, but the incidence dropped to only 5% in cycle 8, suggesting that discontinuation due to this toxicity can be avoided with preemptive dermatological treatment and dose modifications [29]. In the USA FDA review of regorafenib, the mean exposure of M2 and M5 were higher in patients older than 65 years of age in Phase I studies [16].…”
Section: Toxicity Of Regorafenib In Clinical Trial and Community Settingmentioning
confidence: 99%
See 1 more Smart Citation